SANG HYANG SEMARA RATIH AS A SOURCE OF IDE THE CREATION OF BATIK MOTIFS IN CASUAL FASHION - Sinta Dewi; Muhammad Arif Jati Purnomo (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
Sang Hyang Semara Ratih is a symbol for Balinese Hindus.Another parable Sang Hyang Semara ratih is the meeting of spermatozoa with ovum and also the moon and the sun. The purpose of this project entitled “Sang Hyang Semara Ratih Sebagai Sumber Ide Penciptaan Motif Batik Pada Busana Casual” is to describe the idea, create a written batik with the source of the idea to add a variety of Balinese motifs and design casual clothing by applying the Sang Hyang Semara Ratih motif’s through an aesthetic approach. Data information is obtained from literature study and visual review. The method of art creation uses 3 stages of 6 steps, in the form of exploration, design and realization. The output results are: 2 pairs of casual clothes, a draft of scientific article, catalog of works and HaKi for “Batik Sang Hyang Semara Ratih”. The casual clothing created each has a title based on its character and appearance, namely the first pair of works has the title “Angsung Smara” and “Tadhah Sih” with a batik motif entitled “Sasmitamerta”, and the second pair of works has the title “Baskara” and “Basanta” with a batik motif entitled “Candradisti”. Adult women and men from 18 years old to 40 years old is a target for this casual fashion.